Kajian Hubungan antara Struktur Pori Karbon Aktif dan Efisiensi Reagen Pengkhelat pada Ion Logam Berat - Muhsinun Muhsinun; Emsal Yanuar (Varied Knowledge Journal, 2026)
This study aims to quantitatively analyze the relationship between the pore structure of activated carbon and the efficiency of chelating agents in the adsorption of heavy metal ions. Activated carbon derived from durian peel through chemical activation exhibited a specific surface area of 1850–2620 m²/g and a total pore volume of 0.85–1.42 cm³/g, with pore distribution dominated by micropores (60–70%) and mesopores (30–40%). Following modification with EDTA and EDDS, adsorption capacities significantly increased from 78.5 mg/g to 142.3 mg/g for Pb²⁺, from 65.2 mg/g to 118.7 mg/g for Cd²⁺, and from 71.4 mg/g to 126.5 mg/g for Cu²⁺. The maximum removal efficiency reached 94.6% at pH 6 with a contact time of 120 minutes. The Langmuir isotherm model showed a strong fit to the experimental data (R² = 0.981–0.996), with maximum adsorption capacities (qmax) ranging from 130 to 155 mg/g for modified activated carbon. Kinetic analysis revealed that the pseudo-second-order model provided the best fit (R² > 0.99), indicating that chemisorption was the dominant mechanism. The intraparticle diffusion coefficient increased by 35–48% in activated carbon with higher mesopore distribution. Correlation analysis indicated that mesopore volume had a stronger influence on chelation efficiency (r = 0.87) compared to total surface area (r = 0.72). These findings confirm that the synergy between pore structure and chemical modification significantly enhances adsorption efficiency in a measurable and systematic manner.